Dynamic Surface Wetting and Heat Transfer in a Droplet-Particle System of Less Than Unity Size Ratio - Mitra, Subhasish; Evans, Geoffrey (Frontiers in Chemistry, 2018)
Dynamic surface wetting of particles in contact with droplet is a complex phenomenon ubiquitously encountered in many multiphase systems of industrial importance. In this study, we address this aspect by investigating impact behaviour of a water droplet (diameter = 2.9  0.1 mm) in the Weber number range from ~ 4 to 104 on a stationary spherical brass particle (diameter = 10 mm) with and without heat transfer using a combination of high speed imaging and CFD modelling approach. In cold state interactions (20 oC), droplet exhibited oscillatory interfacial motion comprising periodic spreading and recoiling motion. Interactions involving heat transfer were studied in film boiling regime (350 oC) and two outcomes were noted – droplet rebound and disintegration. A coupled Level Set and Volume of Fluid approach based multiphase CFD model was utilised to predict the dynamic spread ratio and transient evolution of droplet shape during the interaction. To capture the complex contact line motion realistically, a continuous time varying profile of experimentally measured dynamic contact angles was used as a wall boundary condition for the cold interactions which provided good agreement with experimentally measured droplet spread ratio. In film boiling regime, droplet spread ratio was correlated to impact Weber number and a power law trend was obtained. Rebound and disintegration outcomes were characterised by the droplet-particle contact time. For simulating interactions in film boiling regime, a constant contact angle in the limit of super-hydrophobic surface was implemented in the CFD model to account for the apparent non-wetting effect due to vapour film formation at the contact area. A sensitivity analysis was performed involving three different contact angle boundary conditions (s=150o, 160o and 170o) to represent the surface hydrophobicity. CFD model predicted interaction outcomes and droplet spread ratios were in reasonable agreement with the experiment at different impact Weber numbers. Increase in particle surface heat flux and corresponding rise in droplet temperature at different impact Weber numbers were also quantified which showed an increasing trend up to a critical Weber number for droplet disintegration.